2013
DOI: 10.1039/c3dt51232k
|View full text |Cite
|
Sign up to set email alerts
|

A new type of paddle-wheel coordination complex

Abstract: In the presence of Na(+) ions, the reaction of the ligand 2-hydroxy-1,3-bis-(3-oxo-3-(2-hydroxyphenyl)-propionyl)-benzene, H5L4, with M(AcO)2 salts (M = Mn, Co) gathers the conditions for the assembly of coordination complexes (NBu4)3[M2Na2(H2L4)3] (M = Mn(II) 1 and Co(II) 2), which exhibit a new paddle-wheel structure. The features of this new category of compounds are discussed as well as their magnetic properties and solution behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…[20] A careful analysis of the literature of zinc carboxylates reveals that discrete triple-blade paddle-wheels with just three symmetrically distributed bridging carboxylates, [Zn 2 (m-O 2 CR) 3 ] are extremely rare. [21,22] Such Full Papers DOI: 10.1002/slct.201601853 paddle-wheel molecules are kinetically less stable due to the open coordination sphere at the metal center. [23] Our earlier studies on 2-hydroxybenzoate (salicylate) have showed that the presence of bulky alkyl groups in the aromatic ring of benzoic acid provides kinetic control over the product formation.…”
Section: Introductionmentioning
confidence: 99%
“…[20] A careful analysis of the literature of zinc carboxylates reveals that discrete triple-blade paddle-wheels with just three symmetrically distributed bridging carboxylates, [Zn 2 (m-O 2 CR) 3 ] are extremely rare. [21,22] Such Full Papers DOI: 10.1002/slct.201601853 paddle-wheel molecules are kinetically less stable due to the open coordination sphere at the metal center. [23] Our earlier studies on 2-hydroxybenzoate (salicylate) have showed that the presence of bulky alkyl groups in the aromatic ring of benzoic acid provides kinetic control over the product formation.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are; a whole category of oxygen based metallohelicates, [4][5][6][7] an entire family of molecular platforms for the construction of supramolecular edices, 3,8 or a novel type of paddle wheel complexes. 9 One subclass of this kind of ligands exhibits two b-diketone groups separated by an m-pyridinediyl spacer (Scheme 1A). Their interesting coordination chemistry is illustrated by an impressive family of heterometallic clusters with a chain-like [M-Ln-M] 7+ core (M 2+ ¼ Cu, Ni; Ln 3+ ¼ any lanthanide) sandwiched by two ligands in the coordination mode shown in Scheme 1B.…”
Section: Introductionmentioning
confidence: 99%
“…However, the few reports on systems showing structural features similar to those of 1 consistently point to weak antiferromagnetic interactions mediated by both triple diazine 33,51,52 and phenoxido bridges. 53,54 To reduce the overparametrization of the problem, we then considered a common set of single-ion parameters for the two crystallographically independent cobalt(II) centers and further assumed the diazine transmitted coupling to be negligible: this amounts to consideration of the system as the sum of two antiferromagnetically coupled dimers with no intradimer…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Finally, the literature on magnetostructural correlations for Co II exchange coupled systems is extremely scarce, due to the ease of parametrization and complexity of the treatment required for a quantitative analysis of magnetic data of Co II centers. However, the few reports on systems showing structural features similar to those of 1 consistently point to weak antiferromagnetic interactions mediated by both triple diazine ,, and phenoxido bridges. , …”
Section: Resultsmentioning
confidence: 99%